The Effect of Profitability, Liquidity, Leverage, Capital Structure, and Company Size on Company Value (Empirical Study of Energy Sector Companies Listed on the IDX 2020-2023) - Hasanah, Nur; Fauzan, Fauzan (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of profitability, liquidity, leverage, capital structure, and firm size on firm value in the energy sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. This study uses a quantitative approach with secondary data in the form of company financial reports. The sampling method used was purposive sampling with a total of 224 observations from 56 companies over four years. Data analysis was performed using multiple linear regression. The results show that leverage, capital structure, and firm size have a significant effect on firm value. Leverage has a negative effect, while capital structure has a positive effect, and firm size has a negative effect on firm value. Meanwhile, profitability and liquidity do not have a significant effect on firm value. These findings imply that energy sector companies need to pay attention to managing their capital structure and debt levels to avoid reducing the company's value in the eyes of investors. Furthermore, large company size does not always reflect high market value if it is not balanced with efficiency and good growth prospects.